K.O. e Amor de Que: Pabllo Vittar entre o combate e a reafirmação de padrões machistas e heteronormativos - Costa, Diego Luiz Back (Universidade do Vale do Rio dos Sinos, 2021)
This work seeks to understand how the aesthetic elements of Pabllo Vittar's music videos contribute to the naturalization of the presence and belonging of the LGBTQIA+ audience in spaces traditionally related to the male and heterosexual universe. The work is divided into three stages, the first being a conceptual deepening about audiovisual and music; the second relating gender and advertising, and the third presenting the characteristics present in the work of Pabllo Vittar from an iconographic and iconological approach to the music videos K.O. and Amor de Que. In the analysis, the scenes and musicality of the music videos were observed, considering aspects such as colors, light, lines, depth, sets, objects, costumes, camera movements, narratives and sounds. It was possible to conclude that these videos make use of stereotypes, based on the presence of Pabllo Vittar in certain environments, to tension sexist and heteronormative behavior, raising discussions about the spaces to be occupied by the LGBTQIA+ audience in audiovisual consumption scenarios.
Keywords: Pabllo Vittar; LGBTQIA+; Machismo; Videoclipe; Publicidade; Chauvinism; Music video; Advertising